Financing of NCD Prevention in LMICs: Jamaica Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: The objective of this study is to estimate spending on non-communicable diseases (NCD) prevention in Jamaica and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Jamaica spent an estimated 1,435 million Jamaican Dollar (JMD) on NCD prevention in 2017-18, constituting around 2.7% of total health spending for the year. Key enablers for NCD prevention revenue mobilization have been earmarked taxes on alcohol, tobacco and gambling, civil society advocacy for prevention efforts, regional cooperation for NCDs, increased prioritization of NCD prevention by the Ministry of Health, awareness campaigns focusing on risk factors, political will and inter-sectoral collaboration. Unhealthy diets remain an underserved area in Jamaica and economic slowdown, opposition from tobacco and alcohol industries remain major barriers to further success at revenue mobilization for NCD prevention. Conclusion: Jamaica has made considerable progress in reorienting its health system for an inter-sectoral effort for NCD prevention, but still continues to spend a small proportion of its health budget on prevention. Fears of investment relocation and lower taxation commitments present obstacles to increased revenue mobilization and prevention spending. Keywords: Noncommunicable diseases, tobacco, behaviour, gambling, employees, incidence, Jamaica, risk factors, diet, tobacco, taxes, fear